2000
DOI: 10.1007/bf02766094
|View full text |Cite
|
Sign up to set email alerts
|

Modern methods for diagnosis ofGardnerella infection

Abstract: Comparison of morphological, bacteriological, serological, and genetic methods for diagnosis of Gardnerella infection in vaginosis showed that the first three methods are preferable, while the genetic method (polymerase chain reaction) is more efficient for identification of Gardnerella vaginalis in culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Makarova et al compared morphological, bacteriological, serological, and genetic methods for the diagnosis of G. vaginalis. They showed that PCR was more efficient for the diagnosis of G. vaginalis (16). Menard (19).…”
Section: Discussionmentioning
confidence: 99%
“…Makarova et al compared morphological, bacteriological, serological, and genetic methods for the diagnosis of G. vaginalis. They showed that PCR was more efficient for the diagnosis of G. vaginalis (16). Menard (19).…”
Section: Discussionmentioning
confidence: 99%